Prevalence and socio-economic determinants of malaria among children under five in Cameroon - Nounouce, Ngako Pamen Joelle; Zakariaou, Njoumemi; Marie-José, Essi; Yollande, Tankeu; Carele, Djofang; Christelle, Bakoue (International Journal Of Community Medicine And Public Health, 2022)
Background: Malaria is a major risk of morbidity and mortality among children under five in Cameroon with 13.7% of deaths in 2017. This paper aims to determine the prevalence and socioeconomic determinants of malaria among children under five in Cameroon. Methods: The study used secondary population data from 5th demographic and health survey (DHS-V). A stratified, 2-stage sampling was implemented and yielded a sample of 4094 children under 5 years of age who underwent a rapid diagnostic test (RDT). The logistic regression model was used to estimate the prevalence and socio-economic determinants of malaria with multivariate descriptive and explanatory analysis. The results were presented in terms of cross tabulations and frequencies and the differences were considered statistically significant at a p<0.05. Results: The results show that 1024 out of 4094 children were tested positive, with a prevalence rate of 25%. There is a regional and residential disparity in malaria prevalence and a child living in a rural area was twice more likely to be infected with malaria. The prevalence of malaria is a function of the socio-economic characteristics of the household, as prevalence decreases as well-being improves from 33.8% among the poor to 13.3% among the rich. Low socio-economic status is a risk factor for malaria infection in children under five in Cameroon. Conclusions: The policy implications are concerned with the reduction of socio-economic disparities, the promotion of free health care and universal health coverage in Cameroon.